Islamic Family Law Review of Contemporary Dowry: Case Study of Mosque Dowry in Indonesian Artist Marriages - Ahmad Alfin Afadi; Abdul Halim; Amar Muhammad (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
The phenomenon of mosque dowry in Indonesian celebrity marriages, with the aim of exploring its validity according to Islamic family law. Dowry, as an essential component in marriage and a symbol of appreciation, has evolved in form, giving rise to mosque dowry, which raises significant questions regarding its legal status. This study uses a case study method with data sources from Islamic scholars' books, interviews with experts, and social media; this study found that mosques must have waqf status, making them unable to be traded, donated, or inherited. This finding is consistent with the legal principle of dowry agreed upon by most scholars of the four schools of thought, namely that the dowry must be in the form of objects that can be traded. Therefore, the mosque dowry is declared invalid. This conclusion is also in line with the opinion of the Chairman of the Fatwa Commission of the Indonesian Ulema Council of East Java, who emphasized the invalidity of the mosque dowry so that the consequence is the obligation to pay a mitsli dowry. However, the marriage remains valid because scholars argue that the dowry is not a condition or pillar of marriage. This study provides critical insight into the implementation of waqf law and Islamic family law in the context of contemporary marriage practices in Indonesia.